Transition metal free catalytic hydroboration of aldehydes and aldimines by amidinato silane - Bisai, Milan; Pahar, Sanjukta; Das, Tamal; Sen, Sakya S. (Dalton Transactions, 2017)
The transition metal free catalytic hydroboration of aldehydes and ketones is very limited and has not been reported with a well-defined silicon(iv) compound. Therefore, we chose to evaluate the previously reported silicon(iv) hydride [PhC(NtBu)2SiHCl2], (1) as a single component catalyst and found that it catalyzes the reductive hydroboration of a range of aldehydes with pinacolborane (HBpin) under ambient conditions. In addition, compound 1 can catalyze imine hydroboration. DFT calculation was carried out to understand the mechanism.

Access to silicon(II)- and germanium(II)-indium compounds - Pahar, Sanjukta; Karak, Suvendu; Pait, Moumita; Raj, K. Vipin; Vanka, Kumar; Sen, Sakya S. (Organometallics, 2018)
Despite the remarkable ability of N-heterocyclic silylene to act as a Lewis base and form stable Lewis adducts with group 13 elements such as boron, aluminum, and gallium, there has been no such comparable investigation with indium and the realization of a stable silylene-indium complex has still remained elusive. Similarly, a germylene-indium complex is also presently unknown. We describe herein the reactions of [PhC(NtBu)(2)SiN-(SiMe3)(2)] (1) and [PhC(NtBu)(2)GeN(SiMe3)(2)] (4) with InCl3 and InBr3 that have resulted in the first silylene-indium complexes, [PhC(NtBu)(2)Si{N(SiMe3)(2)}-> InCl3] (2) and [PhC(NtBu)(2)Si{N(SiMe3)(2)}-> InBr3] (3), as well as the first germylene-indium complexes, [PhC(NtBu)(2)Ge{N(SiMe3)(2)}-> InCl3] (5) and [PhC(NtBu)(2)Ge{N(SiMe3)(2)}-> InBr3] (6). The solid-state structures of all species have been validated by single-crystal X-ray diffraction studies. Note that 5 and 6 are the first structurally characterized organometallic compounds that feature a Ge-In single bond (apart from the compounds in Zintl phases). Theoretical calculations reveal that the Si(II)-> In bonds in 2 and 3 and the Ge(II)-> In bonds in 5 and 6 are dative bonds.

Access to diverse germylenes and a six-membered dialane with a flexible beta-diketiminate - Pahar, Sanjukta; Swamy, V. S. V. S. N.; Das, Tamal; Gonnade, Rajesh G.; Vanka, Kumar; Sen, Sakya S. (Chemical Communications, 2020)
A nacnac-based tridentate ligand containing a picolyl group (L) was employed to isolate chlorogermylene (1). The reaction of1with another equivalent of GeCl2 center dot dioxane surprisingly gave pyridylpyrrolide-based chlorogermylene (2)viaC-N bond cleavage and C-C coupling, while with AlCl3, it afforded a transmetalated product,4. The reaction of L with AlH3 center dot NMe2Et led to an unusual cyclohexane type six-membered dialane heterocycle (5).

Cyanosilylation by compounds with main-group elements: an odyssey - Pahar, Sanjukta; Kundu, Gargi; Sen, Sakya S. (ACS Omega, 2020)
The past few decades have seen remarkable headways in the structural and reaction chemistry of compounds with heavier main-group elements. In recent years, there is an ongoing effort to derive catalytic chemistry involving main-group compounds, driven by their lower costs and higher terrestrial abundances. Here, a survey on the state-of-the-art in the development of cyanosilylation methodology by compounds with heavier main-group elements has been given. Once dominated by transition metals, the field has matured to embrace the majority of the main-group elements including aluminum, silicon, and calcium. Of particular focus will be how the mechanism of cyanosilylation involving compounds with main-group elements differs from those of transition metals.

Stepwise nucleophilic substitution to access saturated N-heterocyclic carbene haloboranes with boron-methyl bonds - Kundu, Gargi; Pahar, Sanjukta; Tothadi, Srinu; Sen, Sakya S. (Organometallics, 2020)
Compounds of boranes with N-heterocyclic carbenes are known, yet little attention has been paid to NHC compounds of boron bearing methyl and halogen moieties together. The reason can be attributed to the hazardous methyldichloroborane (MeBCl2), which ignites in air. We describe here convenient solution-phase access to SIDipp.MeBCl2 (SIDipp = 1,3-bis(2,6-diisopropylphenyl)imidazolin-2-ylidene) (3) by a salt metathesis reaction of SIDipp.BCl3 (2) with MeLi. Replacement of the chlorine atoms of 3 with stepwise addition of AgOTf led to the formation of SIDipp.MeBCl(OTf) (4) and SIDipp.MeB(OTf)2 (5). In the case of 4, all of the substituents on the boron atom are different. Subsequently, we extended our synthetic approach to the amidinate system and prepared PhC(NtBu)2B(Me)Cl (7) from the reaction of PhC(NtBu)2BCl2 (6) with MeLi.

Pyridylpyrrolido ligand in Ge(II) and Sn(II) chemistry: synthesis, reactivity and catalytic application - Pahar, Sanjukta; Sharma, Vishal; Tothadi, Srinu; Sen, Sakya S. (Dalton Transactions, 2021)
In our previous communication, we have reported the synthesis of a new chlorogermylene (B) featuring a pyridylpyrrolido ligand. This study details the preparation of a series of new germylenes and stannylenes starting from B. A transmetallation reaction between B and SnCl2 led to the analogous chlorostannylene (1) with the simultaneous elimination of GeCl2. This is a very unusual example of transmetallation between two elements of the same group. The preparation of 1via lithiation led to the formation of 2 as a side product, where the ortho C-H bond of the pyridine ring was activated and functionalized with a Bu-n moiety. Subsequently, B and 1 were used as precursors to generate germylene (4) and stannylene (5) featuring tris(trimethylsilyl)silyl (hypersilyl) moieties. We also prepared tetrafluoropyridyl germylene (6) by reacting 4 with C5F5N with the simultaneous elimination of (Me3Si)(3)SiF by utilizing the fluoride affinity of the silicon atom. As there is scarcity of Sn(II) compounds as single-site catalysts, we investigated 5 as a catalyst towards the hydroboration of aldehydes, ketones, alkenes and alkynes. All the compounds have been characterized by single-crystal X-ray diffraction and by state of the art spectroscopic studies.

Luminescent magnesium complexes with intra- and inter-ligand charge transfer - Kumar, Rohit; Pahar, Sanjukta; Chatterjee, Joy; Dash, Soumya Ranjan; Gonnade, Rajesh G.; Vanka, Kumar; Sen, Sakya S. (Chemical Communications, 2022)
Herein, we report two 2,2'-pyridylpyrrolide (PyPyrH) ligand supported magnesium complexes (1 and 2), which demonstrate bright luminescence with a quantum yield of 22% and 14% in the solid state, respectively. Theoretical calculations reveal that their emissive properties originate from the intra- and inter-ligand charge transfer.

Tridentate NacNac stabilized tin and nickel complexes: access to a monomeric nickel hydride and its catalytic application - Pahar, Sanjukta; Sharma, Vishal; Mahata, Biplab; George, Christy P.; Sharma, Himanshu; Vanka, Kumar; Sen, Sakya S. (Inorganic Chemistry, 2022)
The transmetalation reaction of picolyl-supported tridentate nacnac germylene monochloride [2,6-iPr2-C6H3NC-(Me)CHC(Me)NH(CH2py)]GeCl (1) (py = pyridine) with SnCl2 results in an analogous stannylene chloride (2). The three -coordinated stannylenium cation [{2,6-iPr2-C6H3NC(Me)CHC-(Me)NH(CH2py)}Sn]+ with SnCl3- as a counteranion (3) has been generated through the abstraction of chloride ligand from 2 using an additional equivalent of SnCl2. Instead of forming a donor-acceptor complex, 2 undergoes a facile redox trans-metalation reaction with Ni(COD)2 (COD = cyclooctadiene) and CuCl to afford analogous nickel and copper complexes [2,6-iPr2-C6H3NC(Me)CHC(Me)NH(CH2py)]MCl [M = Ni (4) and Cu (5)]. The reactions of 4 with potassium tri-sec-butylborohydride (commonly known as K-selectride) and AgSbF6 provide access to monomeric Ni(II) hydride, [2,6-iPr2-C6H3NC(Me)CHC(Me)NH(CH2py)]NiH (6) and a Ni(II) cation, [{2,6-iPr2- C6H3NC(Me)CHC(Me)NH(CH2py)}Ni][SbF6] (7), respectively. 6 was found to be an effective catalyst for the hydroboration of amides.

Tridentate NacNac tames T-shaped nickel(I) radical - Pahar, Sanjukta; Sharma, Vishal; Raj, K. Vipin; Sangole, Mayur P.; George, Christy P.; Singh, Kirandeep; Vanka, Kumar; Gonnade, Rajesh G.; Sen, Sakya S. (Chemistry- a european journal, 2024)
The reaction of a nickel(II) chloride complex containing a tridentate beta-diketiminato ligand with a picolyl group [2,6-iPr2-C6H3NC(Me)CHC(Me)NH(CH2py)]Ni(II)Cl (1)] with KSi(SiMe3)3 conveniently afforded a nickel(I) radical with a T-shaped geometry (2). The compound's metalloradical nature was confirmed through electron paramagnetic resonance (EPR) studies and its reaction with TEMPO, resulting in the formation of a highly unusual three-membered nickeloxaziridine complex (3). When reacted with disulfide and diselenide, the S-S and Se-Se bonds were cleaved, and a coupled product was formed through carbon atom of the pyridine-imine group. The nickel(I) radical activates dihydrogen at room temperature and atmospheric pressure to give the monomeric nickel hydride. A thermally stable, T-shaped, nickel(I) radical was straightforward obtained by reduction of a tridentate nacnac nickel(II) chloride with KSi(TMS)3. The metalloradical character of the compound was demonstrated by the formation of a highly unusual nickeloxaziridine complex upon addition of TEMPO. The Ni(I) species displays a rich chemistry towards activation S-S, and Se-Se bond leading to unusual C-C coupled product as well as dihydrogen activation at room temperature and atmospheric pressure to generate monomeric nickel hydride.+image
Keywords: C-C Bond formation; Hydrogen Activation; Metalloradical; Nickel; Tridentate nacnac